2020
DOI: 10.1038/s41467-020-19767-w
|View full text |Cite
|
Sign up to set email alerts
|

Parabrachial nucleus circuit governs neuropathic pain-like behavior

Abstract: The lateral parabrachial nucleus (LPBN) is known to relay noxious information to the amygdala for processing affective responses. However, it is unclear whether the LPBN actively processes neuropathic pain characterized by persistent hyperalgesia with aversive emotional responses. Here we report that neuropathic pain-like hypersensitivity induced by common peroneal nerve (CPN) ligation increases nociceptive stimulation-induced responses in glutamatergic LPBN neurons. Optogenetic activation of GABAergic LPBN ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 87 publications
(147 reference statements)
7
103
0
Order By: Relevance
“…Crucially, the SPZ has also recently been shown to send projections to the lateral parabrachial (LPB) nucleus in the midbrain (Vujovic et al, 2015). The LPB has been extensively shown to play a vital role in the relay of pain-related information from the spinal cord to the forebrain, and through these connections the LPB appears to mediate emotional and learningbased aspects of pain (Chiang et al, 2020;Sun et al, 2020). As we will elaborate on in this review, the SCN → SPZ → LPB pathway may serve as a circuit substrate through which the circadian system could exert its influence and lead to the reported temporal differences in pain perception and sensitivity across the 24h day.…”
Section: Circadian Rhythmicitymentioning
confidence: 99%
See 3 more Smart Citations
“…Crucially, the SPZ has also recently been shown to send projections to the lateral parabrachial (LPB) nucleus in the midbrain (Vujovic et al, 2015). The LPB has been extensively shown to play a vital role in the relay of pain-related information from the spinal cord to the forebrain, and through these connections the LPB appears to mediate emotional and learningbased aspects of pain (Chiang et al, 2020;Sun et al, 2020). As we will elaborate on in this review, the SCN → SPZ → LPB pathway may serve as a circuit substrate through which the circadian system could exert its influence and lead to the reported temporal differences in pain perception and sensitivity across the 24h day.…”
Section: Circadian Rhythmicitymentioning
confidence: 99%
“…Neuropathic pain and capsaicin pain both can be attenuated following either optogenetic or chemogenetic inhibition (Chiang et al, 2020;Sun et al, 2020). Additionally, driving LPB glutamatergic neurons leads to a neuropathic pain phenotype without the need of injury, but in the case of injury, such neuropathic pain can be halted by stimulating GABAergic neurons in the LPB.…”
Section: Disinhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although activation of the PBN-PVT pathway induced significant anxiety-like behavior, it did not affect the depressive-like behaviors evaluated by the tail suspension test (TST, Figure3−figure supplement 3A) and the forced swimming test (FST, Figure3−figure supplement 3B). Previous studies have revealed that the PBN receives direct projections from the spinal cord and plays a vital role in pain processing (Deng et al, 2020;Sun et al, 2020). We then assessed whether pharmacogenetic activation of the PVT-projecting PBN neurons affects the nociceptive behaviors.…”
Section: Pharmacogenetics Activation Of the Pvt-projecting Pbn Neurons Induces Anxiety-like Behaviors And Freezing Behaviorsmentioning
confidence: 99%